2013
DOI: 10.7567/apex.6.122704
|View full text |Cite
|
Sign up to set email alerts
|

Optical Gain Spectra of a (0001) InGaN Green Laser Diode

Abstract: The optical gain properties of InGaN-based green (512 nm) laser diodes fabricated on (0001) GaN substrates are investigated. Fitting simulations to the experimental gain spectra provides a Gaussian inhomogeneous broadening of 95 meV, an optical confinement factor of 0.006, and an internal loss as low as 10/cm. The remarkable suppression of inhomogeneous broadening and internal loss compensate for the low optical confinement, leading to a low threshold current density of 2.75 kA/cm 2 . The suppressed inhomogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…In addition to the homogeneous broadening, frequently used in ZB QWs [24,63], parametrized here by sech with 10 meV full width at half-maximum (FWHM), we also consider an inhomogeneous Gaussian broadening, attributed to compositional and potential fluctuations. Our choice of Gaussian broadening with 20 meV FWHM is consistent with a decreased broadening for smaller emission wavelengths in (In,Ga)N QW lasers and reported values relevant for wavelengths of ∼415 nm [64] which corresponds to the typical energy of the gain peak in our calculations. Because of the broadening effects, the individual CB1-HH1 and CB1-LH1 transitions that dominate the gain spectra cannot be distinguished [HH1 and LH1 are 10 meV apart, see Fig.…”
Section: Microscopic Spin-dependent Gainsupporting
confidence: 85%
“…In addition to the homogeneous broadening, frequently used in ZB QWs [24,63], parametrized here by sech with 10 meV full width at half-maximum (FWHM), we also consider an inhomogeneous Gaussian broadening, attributed to compositional and potential fluctuations. Our choice of Gaussian broadening with 20 meV FWHM is consistent with a decreased broadening for smaller emission wavelengths in (In,Ga)N QW lasers and reported values relevant for wavelengths of ∼415 nm [64] which corresponds to the typical energy of the gain peak in our calculations. Because of the broadening effects, the individual CB1-HH1 and CB1-LH1 transitions that dominate the gain spectra cannot be distinguished [HH1 and LH1 are 10 meV apart, see Fig.…”
Section: Microscopic Spin-dependent Gainsupporting
confidence: 85%
“…The measurement of optical gain is used to show the change in the efficiency and that the wide QWs can be used in real-life devices. The optical gain in InGaN LDs has been widely studied, and it was shown that it suffers from the green gap problem just as LEDs do. There are two major causes of the decrease of optical gain for long wavelength LDs: (i) “droop” of quantum efficiency and (ii) lower optical confinement factor (Γ). The decrease of Γ is due to a lower refractive index contrast between the alloys as the operating wavelength increases .…”
Section: Optical Gain Of Wide Ingan Qwsmentioning
confidence: 99%
“…39 Note in this respect that the reported inhomogeneous linewidth broadening values of InGaN QWs extracted from gain spectra in state of the art cyan-green wavelength III-nitride LDs indeed exhibit a moderate increase over this wavelength range. 40,41 Finally, let us emphasize that the ability to control the surface morphology and hence the homogeneity of thick InGaN epilayers is extremely relevant in the framework of applications where the minimization of unwanted disorder is critical. This is especially the case when attempts are made to realize laser waveguides, 42 metamorphic layers, 43 or solar cells.…”
Section: -mentioning
confidence: 99%